Improvement of analytical accounting of expenses for maintenance of fixed assets, which are in financial leasing - Kucherkova, Svitlana; Кучеркова, Світлана Олександрівна; Кучеркова, Светлана Александровна (My University, 2020)
In financial leasing fixed assets are reflected in the balance sheet of the lessee. One of the terms of the financial lease agreement is the condition of operation and maintenance, modernization of the leased object and providing information on its technical condition. This stipulates that the lessor has the right to exercise control over the operation and the intended use of the leased asset by the lessee. The latter is obliged to operate the leased property in accordance with the terms of this clause of the contract and the seller's instructions.
Keywords: financial leasing